Oxidant (O(3) + NO(2)) production processes and formation regimes in Beijing - Lu, Keding; Yuanhang Zhang; Su, Hang; Brauers, Theo; Chou, Charles C.; Hofzumahaus, Andreas; Liu, Shaw C.; Kita, Kazuyuki; Kondo, Yutaka; Min Shao; Wahner, Andreas; Wang, Jialin; et al. (Journal of Geophysical Research-AtmospheresJournal of Geophysical Research-Atmospheres, 2010)
For CareBeijing-2006, two sites were established in urban and suburban regions of Beijing in summer 2006. Observations of O(3) and its precursors together with meteorological parameters at both sites are presented. Gross ozone production rate P(O(3)) and sensitivity to nitric oxides (NO(x)) and volatile organic compounds (VOCs) were investigated using an observation-based photochemical box model (OBM). P(O(3)) varied from nearly zero to 120 and 50 ppb h(-1) for urban and suburban sites, respectively. These rates were greater than the accumulation rates of the observed oxidant (O(3) + NO(2)) concentrations. The O(3) episodes typically appeared under southerly wind conditions with high P(O(3)), especially at the urban site. Sensitivity studies with and without measured nitrous acid (HONO) as a model constraint suggested that the estimated P(O(3)) at both sites was strongly enhanced by radical production from HONO photolysis. Both NO(x)- and VOC-sensitive chemistries existed over time scales from hours to days at the two sites. The variation in O(3)-sensitive chemistry was relatively well explained by the ratio of the average daytime total VOC reactivity (k(TVOC)) to NO, with the transition chemistry corresponding to a k(TVOC)/NO value of 2-4 s(-1) ppb(-1). Pronounced diurnal variations in the O(3) production regime were found. In the morning, conditions were always strongly VOC-limited, while in the afternoon, conditions were variable for different days and different sites. The model-calculated results were tested by measurements of H(2)O(2), HNO(3), total OH reactivity, and HO(x) radicals. The OBM was generally capable of correctly simulating the levels of P(O(3)), although it might tend to overpredict the VOC-sensitive chemistry.